(untitled) (ModaPalavra e-periódico, 2008)
Style is the very personal expression of individuality, and has its own language and pace, though, is invisible at first sight. It´s the synthesis of an individual´s experience, becoming personal identity. However, although being unique and personal, style stablishes inumerous combinations with many others´ expressions. Style is at the same time a brand itself and also the spirit of time in all its complexity